Mural Art as Creative Placemaking: A Community Service Initiative for Tourism and Economic Stimulation in Jamblang Old Town - Budhi, Rizki; Nurul Chamidah; Dina Kholis Aziza; Nurhidayah; Wildan Aflah Nabil; Eef Sayfudin; Nanang Sunadi Arta (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2026)
Background: This community service initiative addresses the challenges of declining tourism appeal and underutilized public spaces in Jamblang Old Town, specifically targeting the lack of community engagement and a distinct cultural visual identity in the area. Purpose of the Study: The purpose is to utilize mural art as a creative placemaking strategy to revitalize the area. The objectives are to empower local residents, strengthen cultural awareness, stimulate creative-economic activities, and lay the foundation for community-based tourism. Methods: The program was guided by a Participatory Action Research (PAR) framework. The methodology involved sequential stages: community consultations, co-design of mural themes, site preparation, and collaborative mural production with active resident involvement. Results: The initiative successfully enhanced the visual character of public spaces and fostered a strong sense of community ownership. It generated early tourism interest, increasing the average daily visitors from 8–12 to 25–37 people. The project established a foundational creative ecosystem, creating emerging opportunities for local micro-entrepreneurship and supporting the village's transition toward sustainable, community-based tourism development.